"It’s never easy for the president to get exactly what he wants." : presidential activism and success in the legislative arena during the presidencies of Clinton, Bush, and Obama - Siewert, Markus B. (2018)
Based on an original dataset of 100 important pieces of legislation passed during the three presidencies of William J. Clinton, George W. Bush, and Barack H. Obama (1992-2013), this study explores two sets of questions: (1) How do presidents influence legislators in Congress in the legislative arena, and what factors have an effect on the legislative strategies presidents choose? (2) How successful are presidents in getting their policy positions enacted into law, and what configurations of institutional and actor-centered conditions determine presidential legislative success? The analyses show that in an hyper-polarized environment, presidents usually have to fight an uphill-battle in the legislative arena, getting more involved if they face less favorable contexts and the odds are against them. Moreover, the analyses suggest that there is no silver-bullet approach for presidents' legislative success. Instead, multiple patterns of success exist as presidents - depending on the institutional and public environment - can resort to different combinations of actions in order to see their preferred policy outcomes enacted.